Chemical Strategies in Ecosystem Restoration and Conservation: Exploring Green Alternatives to Chemical Fertilizers and Pesticides - Geng Yilu (MATEC Web of Conferences)
In the context of severe global agri-environmental pollution problems, it is important to explore green alternatives to chemical fertilizers and pesticides. This paper aims to explore and study some alternatives to chemical fertilizers and pesticides to reduce environ-mental pollution and restore the ecosystem. The results of the study show that the use of alter- natives to chemical fertilizers and pesticides has many advantages, such as the ability to effectively improve the soil structure, improve crop yield and quality, reduce the negative impact on the environment, and achieve sustainable agricultural development. Overall, this paper provides new perspectives and in-depth understanding for exploring green alternatives to chemical fertilizers and pesticides. Alternatives to chemical fertilizers and pesticides play an important role in the future green agricultural construction system and will make outstanding contributions to the field of reducing global environmental pollution.